PENGARUH SELF-EFFICACY DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN MELALUI KOMUNIKASI INTERPERSONAL SEBAGAI VARIABEL INTERVENING PADA PDAM KOTA PADANG - Rini Desriyanti; M. Afuan; Bayu Pratama Azka (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
This study aims to determine Self-Efficacy and Work Motivation on Employee Performance through Interpersonal Communication as an intervening variable at PDAM Padang City. The data analysis method uses a questionnaire, with a sample of 73 respondents. The data analysis method used in this study is outer Model analysis, Avarage Variance Extracted (AVE), Reliability Assessment, and Inner Model Testing (Structural Model) using SmartPLS 3.0. The results showed that Self-Efficacy has a positive and significant effect on Interpersonal Comunnication. There is a positive and significant effect between Work Motivation on Interpersonal Communication. There is no positive and significant effect between Self-Efficacy On Employee Performance. There is no positive and significant effect between Work Motivation on Employee Performance. There is a positive and significant effect between Interpersonal Communication On Employee Performance. There is a positive and significant effect between Self-efficacy on Employee Performance through Interpersonal Communication as an intervening variable at PDAM Padang City. There is a positive and significant effect between Work Motivation on Employee Performance through Interpersonal Communication as an intervening variable at PDAM Padang City.